Awareness of malocclusion and desire for orthodontic treatment in 11 to 14 year-old Nigerian schoolchildren and their parents - Kolawole Kikelomo A.; Otuyemi Olayinka D.; Jeboda Sonny O.; Umweni Alice A. (Sciendo, 2023)
To investigate Nigerian children's and their parents' satisfaction with the children's facial and dental appearances and their desire for orthodontic treatment, and to compare their assessments of treatment need with those determined by an orthodontist.